Preparation method of high-performance flow battery composite membrane based on perfluorinated sulfonic acid resin and two-dimensional material

By combining perfluorosulfonic acid resin with two-dimensional materials, the solution casting process is used to prepare the flow battery composite film, which solves the shortcomings of the existing separators in terms of ion conduction and cost, and achieves an efficient and low-cost flow battery separator.

CN119684645APending Publication Date: 2025-03-25INST OF METAL RESEARCH - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311237410.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing flow battery separators have shortcomings in ion conduction, water absorption, swelling rate, area resistance and ion permeability, resulting in low battery efficiency and high cost.

Method used

A composite film preparation method combining perfluorosulfonic acid resin and two-dimensional materials (such as MXene and graphene) is used to regulate process parameters through the solution casting process to prepare a high-performance liquid flow battery composite film.

Benefits of technology

It achieves high ion selective permeability and conductivity, while reducing the cost of the diaphragm, and is suitable for high current density flow batteries, improving battery efficiency and long-term performance stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of flow battery diaphragms, in particular to a preparation method of a high-performance flow battery composite membrane based on perfluorinated sulfonic acid resin and a two-dimensional material. According to the method, a solution casting method is adopted, and the dispersion degree of a filler in a perfluorosulfonic acid resin matrix is improved by optimizing the dosage of perfluorosulfonic acid resin, regulating and controlling the addition amount of a two-dimensional material in the perfluorosulfonic acid resin and improving the process, so that the composite film is prepared, the cost is reduced, and the electrochemical performance of the composite proton exchange membrane is improved. The proton exchange membrane prepared by utilizing a solution casting method has relatively good conductivity and relatively good vanadium resistance, the battery performance of the flow battery is optimized, and a new thought for development of a flow battery diaphragm especially under high current density is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid flow battery diaphragms, and specifically to a method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional materials. Background Art

[0002] As a new type of secondary battery, redox flow battery is considered to be one of the most suitable technologies for large-scale long-term energy storage due to its independent power and energy, intrinsic safety, and easy management of battery modules. In recent years, the technical and economic benefits of flow batteries in the field of new energy storage have gradually emerged and are experiencing rapid development.

[0003] The flow cell has a unique sandwich structure design, with a diaphragm in the middle and inert electrodes and other accessories and electrolyte storage containers on both sides of the membrane. The diaphragm is the core component of the flow battery, which is used to separate the positive and negative redox species and allow H + or OH - Migration completes the loop. It not only directly affects the battery efficiency, but also determines the cost and stability of the battery. The ideal diaphragm should have the following good properties: high ion conductivity, low water absorption, swelling rate, area resistance and ion permeability, good chemical stability and low cost. The resistance generated by the diaphragm's own ion conduction accounts for a large part of the entire battery stack's internal resistance (30-50%). Therefore, by reducing the thickness of the diaphragm to reduce the surface resistance and adding fillers to ensure a smaller vanadium ion permeability, the ion selectivity of the diaphragm can be effectively improved, the performance of the flow battery can be improved and the cost can be reduced.

[0004] Two-dimensional materials (transition metal carbonitrides MXene and graphene) have high specific surface area, excellent conductivity, abundant active centers and excellent chemical stability. Their good combination with perfluorosulfonic acid (PFSA) resin matrix can reduce the size of ion channels and reduce the penetration of vanadium ions. Reducing the use of PFSA resin and reducing the thickness of the composite membrane can reduce the surface resistance, thereby greatly optimizing the performance of the diaphragm. In addition, MXene and graphene materials can also be surface functionalized to promote proton transfer, promote proton conduction of the composite membrane, and improve the proton conductivity of the composite membrane, thus showing great application potential in polymer membrane materials. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional materials. With PFSA resin and two-dimensional materials as the main raw materials, a series of PFSA / two-dimensional material composite proton exchange membranes are prepared by solution casting membrane process and adjusting process parameters. While ensuring high ion selective permeability and high conductivity of the diaphragm, the cost of the diaphragm is reduced, and it can be applied to liquid flow batteries, especially under high current density working conditions.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a high-performance flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional materials comprises the following steps: (1) preparing a two-dimensional layered material, wherein the two-dimensional material comprises a transition metal carbonitride MXene and graphene; (2) dissolving the perfluorosulfonic acid resin in an organic solvent under magnetic stirring to prepare a resin solution with a concentration of 2-5 wt.%; (3) adding the resin solution obtained in step (2) to the two-dimensional layered filler, and subjecting the mixture to ultrasonic treatment and stirring to uniformly disperse the filler in the resin matrix; (4) Controlling the drying temperature and time parameters of the solution obtained in step (3) to prepare a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional layered materials.

[0007] Furthermore, in the above-mentioned method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material, in step (1), a transition metal carbonitride is prepared by etching, specifically one of the MAX phases Ti3AlC2, Ti3AlCN, Ti2AlC, Ti2AlN, Mo2AlC, V2AlC, Ti4AlN3, Mo4AlC3, V4AlC3, Nb4AlC3 and Ta4AlC3, and is etched by one of the solutions selected from hydrofluoric acid, a fluorine acid solution mixed with (LiF, KF, CaF2, NaF) and HCl or H2SO4, and a difluoride solution (NH4HF2, KHF2, NaHF2), wherein the solution concentration is 10 to 40 wt%; the mass ratio of the MAX phase to the etching solution is 1:10 to 30; the etching time is 24 to 72 h, and the etching temperature is 25 to 60 °C.

[0008] Furthermore, in the above-mentioned method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material, in step (1), the MXene material is cleaned by filtration or centrifugation, and the pH of the aqueous solution after cleaning is 6 to 7; after cleaning, it is dried at a temperature of 30 to 100°C and a drying time of 12 to 36 hours.

[0009] Furthermore, in the above-mentioned method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional materials, in step (1), the graphene material is commercially available graphene oxide or functionalized graphene oxide.

[0010] Furthermore, in the above-mentioned method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material, in step (2), the organic solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0011] Furthermore, in the above-mentioned method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material, in step (3), the mass ratio of the added two-dimensional material to the perfluorosulfonic acid resin is 1:99 to 10:90.

[0012] Furthermore, in the above-mentioned method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material, in step (3), the ultrasonic treatment frequency is 20~60kHz and the treatment time is 0.5~5h.

[0013] Furthermore, in the above-mentioned method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material, in step (3), the stirring speed is 100~1000rpm.

[0014] Furthermore, in the above-mentioned method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material, in step (4), a solution casting method is used, the membrane drying temperature is 100 to 160°C, the drying time is 1.5 to 3 hours, and the membrane thickness is 25 to 35 μm.

[0015] Furthermore, the above-mentioned method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional materials, the liquid flow batteries suitable for the composite membrane include iron-chromium, all-vanadium, zinc-iron, all-iron, zinc-bromine, sodium polysulfide / bromine, titanium-manganese or organic system liquid flow batteries.

[0016] The design concept of the present invention is: The PFSA resin is made into a solution of a certain concentration, and two-dimensional layered materials such as MXene or graphene are added thereto, and the solution is cast to solidify the solution into a film. The amount of PFSA resin used is reduced to reduce the thickness of the diaphragm to reduce the surface resistance, while reducing the penetration of vanadium ions in the side reaction. By optimizing the addition content of the two-dimensional material in the PFSA resin and the process parameters of solution casting, the combination of the filler and the PFSA resin is optimized, so that the filler is evenly distributed in the PFSA resin and well combined with the resin, achieving a balance between high conductivity and low ion selective permeability.

[0017] The advantages and beneficial effects of the present invention are as follows: 1. The composite proton exchange membrane is prepared by solution casting in the present invention. The equipment and process used in the method are simple, the use of resin is reduced, the production cost is reduced, and the method is suitable for the industrial application of liquid flow battery diaphragms; 2. The present invention prepares a composite proton exchange membrane with a thickness of 25 to 35 μm, improves the conductivity of the membrane and reduces the cost of the membrane; by optimizing the addition amount of the two-dimensional layered filler and the solution casting process, the filler is evenly distributed in the resin matrix, effectively hindering the penetration of ions, and comprehensively improving the ion selectivity of the proton exchange membrane. The most important thing is that its battery efficiency has been greatly improved, and the long-term performance is also relatively stable; 3. The proton exchange membrane prepared by the present invention has good conductivity and vanadium resistance. On the basis of PFSA film, it improves the performance of the liquid flow battery and reduces the production cost. At the same time, it meets the use conditions of the liquid flow battery, provides a new idea for the development of liquid flow battery diaphragms, and is also of great significance for reducing the cost of energy storage systems. DETAILED DESCRIPTION

[0018] In the specific implementation process, the present invention adds an appropriate amount of two-dimensional material to the PFSA matrix, and uses a solution casting method to solidify the composite resin solution into a film. In order to further understand the present invention, the present invention is described below in conjunction with examples, but the examples are only for further elaboration of the characteristics and advantages of the present invention, rather than for limiting the claims of the present invention.

[0019] Example 1 In this embodiment, the preparation method of the high-performance flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material is as follows: (1) Preparation of MXene material Ti3C2T x Specifically, the MAX phase Ti3AlC2 was slowly poured into a 40% HF solution, 1gTi3AlC2 required 20ml HF solution, etched at 60°C for 24h, washed by multiple centrifugation until the pH of the supernatant was 6, and then kept in an oven at 80°C for 12h; (2) dissolving perfluorosulfonic acid resin in N,N-dimethylformamide under magnetic stirring to prepare a resin solution with a concentration of 3 wt.%; (3) Add the resin solution obtained in step (2) to the filler obtained in step (1), perform ultrasonic treatment at 40kHz for 3h, and magnetically stir at 300rpm for 5h to uniformly disperse the filler in the resin. The proportion of MXene in the solution is 2wt.% (4) The solution obtained in step (3) was heated to 140° C. in an oven and cast onto a glass plate. The mixture was kept at this temperature for 3 h to solidify into a membrane. The thickness of the composite proton exchange membrane was 30 μm.

[0020] In this embodiment, the obtained composite proton exchange membrane is a two-dimensional material Ti3C2T x It is evenly distributed on both macro and micro scales, and its color is light black. It is assembled into an all-vanadium liquid flow battery and the current density is 300mA / cm -2Under the constant current charge and discharge test conditions, the coulombic efficiency of the battery using the composite proton exchange membrane is 97.3% and the energy efficiency is 82.7%.

[0021] Example 2

[0022] In this embodiment, the preparation method of the high-performance flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material is as follows: (1) The MAX phase Ti3AlC2 was placed in a 20% HF solution with a mass ratio of Ti3AlC2 to HF solution of 1:20, and etched at room temperature for 36 h. The filtrated solution was cleaned by suction filtration until the pH value of the filtered water solution was 6, and then kept in an oven at 30°C for 24 h. (2) dissolving perfluorosulfonic acid resin in N,N-dimethylformamide under magnetic stirring to prepare a resin solution with a concentration of 2 wt.%; (3) Add the resin solution obtained in step (2) to the filler obtained in step (1), perform ultrasonic treatment at 60kHz for 1h, and magnetically stir at 500rpm for 2h to uniformly disperse the filler in the resin. The proportion of MXene in the solution is 3wt.%; (4) The solution obtained in step (3) was heated in an oven to 100° C. and cast onto a glass plate. The mixture was kept at this temperature for 5 h to solidify into a membrane. The thickness of the composite proton exchange membrane was 30 μm.

[0023] In this embodiment, the obtained composite proton exchange membrane is a two-dimensional material Ti3C2T x It is evenly distributed at both macro and micro scales, and its color is black, which is darker than that of 2wt%. It is assembled into an all-vanadium liquid flow battery, and at a current density of 300mA / cm -2 Under the constant current charge and discharge test conditions, the coulombic efficiency of the battery using the composite proton exchange membrane is 97.6% and the energy efficiency is 80.3%.

[0024] Example 3

[0025] In this embodiment, the preparation method of the high-performance flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material is as follows: (1) 0.2 g of graphene oxide and 2.0 g of NaH were added to 250 ml of anhydrous tetrahydrofuran and stirred at 60 °C for 6 h. Then 2.0 g of 1,3-propane sultone was added and stirred at 80 °C for 24 h. Finally, the filtered residue was immersed in 3 wt% HCl solution for 12 h, washed with ethanol several times, and dried in vacuum at 80 °C for 24 h. (2) dissolving perfluorosulfonic acid resin in N,N-dimethylformamide under magnetic stirring to prepare a resin solution with a concentration of 2 wt.%; (3) Add the resin solution obtained in step (2) to the filler obtained in step (1), perform ultrasonic treatment at 100 kHz for 0.5 h, and perform magnetic stirring at 400 rpm for 3 h to uniformly disperse the filler in the resin. The proportion of graphene in the solution is 3 wt.%; (4) The solution obtained in step (3) was heated to 120° C. in an oven and cast onto a glass plate. The mixture was kept at this temperature for 4 h to solidify into a membrane. The thickness of the composite proton exchange membrane was 35 μm.

[0026] In this embodiment, the obtained composite proton exchange membrane has a uniform distribution of fillers on a macroscopic level and is also light black in color. It is assembled into an all-vanadium liquid flow battery and the current density is 300 mA / cm -2 Under the constant current charge and discharge test conditions, the energy efficiency of the battery using the composite proton exchange membrane is 83.1%. Example 4

[0027] In this embodiment, the preparation method of the high-performance flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material is as follows: (1) 0.05 g of graphene oxide was ultrasonically dispersed in 25 ml of N,N-dimethylformamide for 1 h, then 75 ml of EDA was added and refluxed at 80 °C for 24 h, and then the unreacted EDA was washed with ethanol. After cooling to room temperature, it was filtered and the residue was washed with ethanol until the pH became neutral, and finally dried at 50 °C for 24 h under vacuum; (2) dissolving perfluorosulfonic acid resin in N,N-dimethylacetamide under magnetic stirring to prepare a resin solution with a concentration of 3 wt.%; (3) Add the resin solution obtained in step (2) to the filler obtained in step (1), perform ultrasonic treatment at 300kHz for 1 hour, and perform magnetic stirring at 300rpm for 4 hours to uniformly disperse the filler in the resin. The proportion of graphene in the solution is 5wt.%; (4) The solution obtained in step (3) was heated to 120° C. in an oven and cast onto a glass plate. The mixture was kept at this temperature for 4 h to solidify into a membrane. The thickness of the composite proton exchange membrane was 25 μm.

[0028] In this embodiment, the obtained composite proton exchange membrane has a uniform distribution of fillers on a macroscopic level and is also light black in color. It is assembled into an all-vanadium liquid flow battery and the current density is 300 mA / cm -2 Under the constant current charge and discharge test conditions, the energy efficiency of the battery using the composite proton exchange membrane is 78.9%.

Claims

1. A method for preparing a high-performance flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional materials, characterized in that: The method comprises the following steps: (1) preparing a two-dimensional layered material, wherein the two-dimensional material comprises a transition metal carbonitride MXene and graphene; (2) dissolving the perfluorosulfonic acid resin in an organic solvent under magnetic stirring to prepare a resin solution with a concentration of 2-5 wt.%; (3) adding the resin solution obtained in step (2) to the two-dimensional material, subjecting it to ultrasonic treatment and stirring treatment to uniformly disperse the filler in the resin matrix; (4) Controlling the drying temperature and time parameters of the solution obtained in step (3) to prepare a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional materials.

2. The method for preparing a high-performance flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material according to claim 1, characterized in that: In step (1), a transition metal carbonitride is prepared by etching, specifically one of the MAX phases Ti3AlC2, Ti3AlCN, Ti2AlC, Ti2AlN, Mo2AlC, V2AlC, Ti4AlN3, Mo4AlC3, V4AlC3, Nb4AlC3 and Ta4AlC3, and is etched by one of the solutions of hydrofluoric acid, a fluorine-containing acid solution mixed with (LiF, KF, CaF2, NaF) and HCl or H2SO4, and a difluoride solution of (NH4HF2, KHF2, NaHF2), wherein the solution concentration is 10 to 40 wt%; the mass ratio of the MAX phase to the etching solution is 1:10 to 30; the etching time is 24 to 72 h, and the etching temperature is 25 to 60 ° C.

3. The method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material according to claim 1, characterized in that: In step (1), the MXene material is cleaned by filtration or centrifugation, and the pH of the aqueous solution after cleaning is 6 to 7; after cleaning, it is dried at a temperature of 30 to 100° C. and a drying time of 12 to 36 hours.

4. The method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material according to claim 1, characterized in that: In step (1), the graphene material is commercially available graphene oxide or functionalized graphene oxide.

5. The method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material according to claim 1, characterized in that: In step (2), the organic solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

6. The method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material according to claim 1, characterized in that: In step (3), the mass ratio of the added two-dimensional material to the perfluorosulfonic acid resin is 1:99 to 10:

90.

7. The method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material according to claim 1, characterized in that: In step (3), the ultrasonic treatment frequency is 20-60 kHz, and the treatment time is 0.5-5 h.

8. The method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material according to claim 1, characterized in that: In step (3), the stirring speed is 100-1000 rpm.

9. The method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material according to claim 1, characterized in that: In step (4), a solution casting method is used, the film drying temperature is 100 to 160° C., the drying time is 1.5 to 3 hours, and the film thickness is 25 to 35 μm.

10. The method for preparing a high-performance liquid flow battery composite membrane based on perfluorosulfonic acid resin and two-dimensional material according to claim 1, characterized in that: The composite membrane is applicable to liquid flow batteries including iron-chromium, all-vanadium, zinc-iron, all-iron, zinc-bromine, sodium polysulfide / bromine, titanium-manganese or organic system liquid flow batteries.

Citation Information

Patent Citations

  • Composite graphene ion exchange membrane for flow battery and preparation method thereof

    CN103219533A

  • Polytetrafluoroethylene-based ion exchange membrane for vanadium batteries, and its making method

    CN104332642A

  • Sulfonation graphene and perfluorosulfonic acid resin composite proton exchange membrane and preparation method thereof

    CN104868141A

  • High temperature resistant proton exchange membrane based on sulfonated graphene and preparation method therefor

    CN104927225A

  • Component modulation method of perfluorosulfonic acid resin membrane preparation liquid and prepared proton exchange membrane

    CN110148769A

Cited By

  • High-ion-selectivity perfluorosulfonic acid ionic membrane for vanadium battery as well as preparation method and application of high-ion-selectivity perfluorosulfonic acid ionic membrane

    CN122025692A